An Experience in the Teaching of Language Learning Strategies - Nahum Samperio Sánchez (Voces y Silencios: Revista Latinoamericana de Educación)
This document originated from the development of my doctoral thesis. I decided to put into practice what I had learned in my research on learning strategies within the context in which I was teaching at that time. In addition to observing its impact on students, this experience allowed me to acquire first-hand knowledge teaching language learning strategies outside the limits of my experimental research. My testimony tells about my involvement and my perceptions I had in teaching English language learning strategies within a private company environment. My testimony is not a rigorous analysis of research data. Pseudonyms have been used to protect the identity of learners.